Probing into the Economic Opportunity Programs for persons with Visual Impairmant (VI) the lens of collaborative governance in Mandaue City, Cebu, Philippines - Abis, River B.; Andus, Blessie Rae E.; Bulante, Stephany Jen C.; Dungog-Cuizon, Ana Leah; Olivar, Angel May L.; Prieto, Era Luz Maria M. (Cebu City College of Social Sciences, University of the Philippines Cebu, 2023)
The COVID-19 pandemic has negatively impacted the livelihood and employment opportunities of Persons with Visual Impairment (VIs) working as massage therapists in the Philippines. Initiatives from both the public and private sectors to aid the VIs are existing. However, the available program-based assistance further limits the alternative livelihoods for the sector. This paper seeks to describe the programs and projects initiated by the government towards the economic opportunities of VIs. Further, it probes into the collaboration, or the lack thereof, between the governance triad in implementing said programs in Mandaue City, Cebu, Philippines. The study identified that the existing programs provided by the government for the VIs are limited and selective due to the insufficiency of budget allocation for disability-specific programs and unavailability of data on PWDs. Moreover, the collaboration carried out by the governance triad for the economic opportunity programs has not yet reached the level of institutionalization. As such, a local collaborative governance framework is recommended to commence the institutionalization process of collaboration as a governance framework among the three actors in aiding the VIs, thus forwarding inclusive governance in promoting social development and sustainability.
Thesis (Bachelor of Arts in Political Science) -- University of the Philippines Cebu, April 2023.
Includes bibliographical references and appendices.